Determinants of Partner Work Productivity at The Central Statistics Agency of Labuhanbatu District - Hansyah, Praida; Siregar, Firman Martua (Pusat P2M Politeknik Negeri Batam, 2024)
Organizations that pay attention to work productivity are organizations that in human resources have succeeded in making good use of all the capabilities of their human resources effectively and efficiently. The purpose of this study is to prove the effect of Recruitment and Selection and Human Resources Quality on Work Productivity of increasingly dynamic organizations. The number of samples is 100 samples. The data collection technique was carried out by providing a list of questions or questionnaires online google form with sampling techniques that qualified this research was purposive sampling with SmartPLS data analysis. The results of the research hypothesis test that Recruitment and Selection do not affect Work Productivity both positively and significantly. Other test results of HR Quality variables have a decent significance on Work Productivity. Finally, this study succeeded in providing information that between Recruitment and Selection with HR Quality has a very strong correlation